A developmental perspective on the ideal of reason in American constitutional law - Dailey, Anne C. (2016)
The ideal of reason is central to contemporary accounts of citizenship in American constitutional law. The individual capacity for reasoned choice lies closely aligned with the constitutional values of personal liberty and democratic self-government as they have evolved in Supreme Court decisions over the past century. Yet as presently conceived, the ideal of reason in constitutional law overlooks the process by which individuals actually acquire the capacity to choose their own values and commitments or to engage in reasoned thinking about collective ends. This paper argues that we cannot hope to sustain and foster a constitutional polity committed to the principles of individual liberty and democratic self-government without knowing something about how individual citizens come to possess this requisite skill of mind. A developmental perspective on reason in constitutional law provides a framework for examining the source and contours of the psychological skills that make it possible to lead an autonomous, self directed life and to participate meaningfully in the processes of democratic self-government. Developmental psychology, together with research in related fields, provides empirical support for the proposition that the psychological capacity for reasoned thinking has its roots in the early caregiving relationship. Thus, a comprehensive and integrated constitutional family law must recognize the role of early caregiving in the political socialization of children. This developmental approach offers a substantial reworking of constitutional doctrine in the areas of family privacy, parental rights, congressional power, and affirmative welfare rights.